Designing a Responsive Talent Development Environment: Case study of the Iraqi Federal Board of Supreme Audit - Aldarraji, Isam Khayoon Hassoon; sani, Mohsen Alizadeh; Hosseini, Aboalhasan; Shirkhodaia, Meisam (Journal of Ecohumanism, 2024)
Given the rapid transformations and increasing challenges facing Supreme Audit Institutions (SAIs), the need for flexible and innovative work environments that can attract and develop talents to achieve organizational efficiency and sustainability emerges. The purpose of the study was to create a work environment that encourages talents within the Bureau, which contributes to the sustainability of performance and the achievement of organizational goals. It aims to design a work environment that enables the attraction and development of talents to achieve organizational performance sustainability and enhance innovation and efficiency in the Federal Board of Supreme Audit (FBSA) Using a qualitative methodology based on the Thematic Extraction Method (TEM), various data were collected and analysed. The study conducted interviews with 12 experts, this category of experts included general managers, assistant general managers, and experts from public departments, and they were selected through purposeful sampling, which contributed to providing in-depth data on the requirements of the ideal work environment to support talent development. The analysis process began with coding the data through the following steps: extracting the primary axes, refining them, and classifying them to reach the basic concepts that clarify the dimensions of the required talent development environment from the interview data. The study came up with a design for talent development environment consisting of nine dimensions: the first dimension is providing work tools and infrastructure, then the dimension of searching for and attracting talents, then the dimension of training and developing talents, then the dimension of motivating talents (reward and promotion), then the dimension of knowledge sharing. Then the dimension of identifying talent development opportunities, then the dimension of talent sharing, then effective leadership, and the last in order of importance in the order is the dimension of perceived quality. This approach contributes to improving the quality of financial regulatory services and enhancing the organizational efficiency of the Authority.